2021
DOI: 10.5194/acp-2020-1017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insight into PM<sub>2.5</sub> Sources by Applying Positive Matrix Factorization (PMF) at an Urban and Rural Site of Beijing

Abstract: Abstract. This study presents the source apportionment of PM2.5 performed by PMF on data collected at an urban (Institute of Atmospheric Physics – IAP) and a rural site (Pinggu-PG) in Beijing as part of the Atmospheric Pollution and Human Health in a Chinese megacity (APHH-Beijing) field campaigns. The campaigns were carried out from 9th November to 11th December 2016 and 22nd May to 24th June 2017. The PMF included both organic and inorganic species, and a seven-factor output provided the most reasonable solu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 94 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…In addition, the concentrations of OOA1 and OOA3 were higher in daytime, implying the effect of photochemical processing. The variations in OOA2 tracked well with C 2 H 2 O + 2 (R = 0.89), an aqueousprocessing-related fragment ion (Sun et al, 2016), indicating that OOA2 was an OA factor associated with aqueousphase processing. Previous studies suggested that aqueousphase processing plays an important role in the formation of nitrogen-containing compounds (Xu et al, 2017).…”
Section: Comparison With Source Apportionment Results From Ams-pmfmentioning
confidence: 72%
See 3 more Smart Citations
“…In addition, the concentrations of OOA1 and OOA3 were higher in daytime, implying the effect of photochemical processing. The variations in OOA2 tracked well with C 2 H 2 O + 2 (R = 0.89), an aqueousprocessing-related fragment ion (Sun et al, 2016), indicating that OOA2 was an OA factor associated with aqueousphase processing. Previous studies suggested that aqueousphase processing plays an important role in the formation of nitrogen-containing compounds (Xu et al, 2017).…”
Section: Comparison With Source Apportionment Results From Ams-pmfmentioning
confidence: 72%
“…In order to be compared with the source apportionment results of OC in this study from the CMB model, the OA concentrations from the AMS-PMF were converted to OC based on various OA/OC ratios measured in Beijing: 1.35 for CCOA/CCOC (coal combustion organic carbon), 1.31 for HOA/HOC (hydrocarbon-like organic carbon) (Sun et al, 2016), 1.38 for COA/COC (cooking organic carbon), 1.58 for BBOA/BBOC (biomass burning organic carbon) (W. , and 1.78 for OOA/OOC (oxidized organic carbon; Huang et al, 2010). The concentrations of OA and corresponding OC from AMS-PMF analysis are presented in Table 3.…”
Section: Comparison With Source Apportionment Results From Ams-pmfmentioning
confidence: 99%
See 2 more Smart Citations